Preventive effect of Lactobacillus johnsonii YH1136 against uric acid accumulation and renal damages - Zhang, Xingting; Jiang, Junliang; Xin, Jinge; Sun, Ning; Zhao, Zhifang; Gan, Baoxing; Jiang, Yi; Gong, Xuemei; Li, Hao; Ma, Hailin; Ni, Xueqin; Chen, Yu; et al. (Frontiers in Microbiology, 2024)
Hyperuricemia (HUA) is a prevalent metabolic disorder whose development is associated with intestinal microbiota. Therefore, probiotics have emerged as a potential and safe approach for lowering uric acid (UA) levels. However, the underlying mechanisms of many effective probiotic strains remain unknown. Therefore, this study aimed to investigate microbiota alterations in each intestinal segment during HUA to identify the most affected segment and potential probiotic strains for treatment. Overall, HUA resulted in a significant decrease in the total diversity of all intestinal segments. When each intestinal segment was analyzed individually, the reduction in diversity was only significant in the cecum and colon sections. RDA analysis showed that lactobacilli in the rat colon exhibited a strong correlation with model group, suggesting that Lactobacillus may play an important role in HUA. Consequently, the preventive effects of Lactobacillus johnsonii YH1136 against HUA were investigated. The results showed that administering Lactobacillus johnsonii YH1136 effectively reduced serum UA levels in vivo by inhibiting hepatic xanthine oxidase (XOD) activity and promoting renal ABCG2 transporter expression. Moreover, supplementation with Lactobacillus johnsonii YH1136 significantly ameliorated pathological damage in the kidney and liver, thereby reducing UA accumulation. These findings highlight the potential of Lactobacillus as a key connector between HUA and the gut microbiota, providing compelling evidence for Lactobacillus johnsonii YH1136 as a potential probiotic treatment for HUA via gut-kidney axis.